Finite element study of the proximal femur with retained trochanteric gamma nail and after removal of nail - B. Mahaisavariya (2018)
This study aims to evaluate the stress and strain distributions in the healed proximal femur after fixation with a trochanteric gamma nail (TGN) and after TGN removal, using the finite element method. The stress distributions in the proximal femur with retained TGN and after TGN removal were very similar. The strain and the strain energy density in the femoral neck region with retained TGN were much higher than in the lag screw hole at the subtrochanter and the distal locking screw hole at the proximal femur, and even higher after TGN removal. Stair climbing resulted in higher strain and higher strain energy density at the femoral neck than normal walking. The conclusion can be drawn that removal of the TGN may result in high risk of femoral neck fracture. © 2006 Elsevier Ltd. All rights reserved.